A novel concept for CT with fixed anodes (FACT): Medical imaging based on the feasibility of thermal load capacity - Kellermeier, Markus; Bert, Christoph; Müller, Reinhold (Physica Medica, 2015)
Focussing primarily on thermal load capacity, we describe the performance of a novel fixed anode CT (FACT) compared with a 100 kW reference CT. Being a fixed system, FACT has no focal spot blurring of the X-ray source during projection. Monte Carlo and finite element methods were used to determine the fluence proportional to thermal capacity. Studies of repeated short-time exposures showed that FACT could operate in pulsed mode for an unlimited period. A virtual model for FACT was constructed to analyse various temporal sequences for the X-ray source ring, representing a circular array of 1160 fixed anodes in the gantry. Assuming similar detector properties at a very small integration time, image quality was investigated using an image reconstruction library. Our model showed that approximately 60 gantry rounds per second, i.e. 60 sequential targetings of the 1160 anodes per second, were required to achieve a performance level equivalent to that of the reference CT (relative performance, RP = 1) at equivalent image quality. The optimal projection duration in each direction was about 10 ?s. With a beam pause of 1 ?s between projections, 78.4 gantry rounds per second with consecutive source activity were thermally possible at a given thermal focal spot. The settings allowed for a 1.3-fold (RP = 1.3) shorter scan time than conventional CT while maintaining radiation exposure and image quality. Based on the high number of rounds, FACT supports a high image frame rate at low doses, which would be beneficial in a wide range of diagnostic and technical applications.
EVALuna2:18269

Assessment of the implant geometry in fractionated interstitial HDR breast brachytherapy using an electromagnetic tracking system - Kellermeier, Markus; Fietkau, Rainer; Strnad, Vratislav; Bert, Christoph (Brachytherapy, 2018)
PURPOSE: During the partial-breast treatment course by interstitial brachytherapy, electromagnetic tracking (EMT) was applied to measure the implant geometry. Implant-geometry variation, choice of reference data, and three registration methods were assessed. METHODS AND MATERIALS: The implant geometry was measured in 28 patients after catheter implantation (EMTbed), during CT imaging (EMTCT), and in each of up to n = 9 treatment fractions (EMTF(k), k = 1, 2,… n). EMTF(k) were registered to the planned implant reconstruction (CTplan) by using all dwell positions (DPs), the button centers, or three fiducial sensors on the patient's skin. Variation in implant geometry obtained from EMTF(k) was assessed for EMTbed, EMTCT, and CTplan. RESULTS: EMT was used to measure 3932 catheters. A duration of 6.5 ± 1.7 min was needed for each implant measurement (mean, 17 catheters) plus setup of the EMT system. Data registration based on the DP deviated significantly lower than registration on button centers or fiducial sensors. Within a registration group, there was a <0.5-mm difference in the choice of reference data. Using CTplan as reference for registration, the mean residual distance of DPs on EMT-derived DPs was found at 2.1 ± 1.6 mm (EMTbed), 1.3 ± 0.9 mm (EMTCT), and 2.5 ± 1.5 mm (EMTF(k)). CONCLUSIONS: EMT can assess the implant geometry in high-dose-rate interstitial brachytherapy breast treatments. EMTbed, EMTCT, and CTplan data can serve as reference for assessment of implant changes.
EVALuna2:36444

Differences in Dose Coverage and Uniformity in Fractionated High-Dose-Rate Interstitial Breast Brachytherapy Based on EMT Measurements - Kellermeier, Markus; Hofmann, B.; Strnad, Vratislav; Bert, Christoph (2016)
EVALuna2:33047

Electromagnetic tracking for treatment verification in interstitial brachytherapy - Bert, Christoph; Kellermeier, Markus; Tanderup, Kari (Journal of Contemporary Brachytherapy, 2016)
Electromagnetic tracking (EMT) is used in several medical fields to determine the position and orientation of dedicated sensors, e.g., attached to surgical tools. Recently, EMT has been introduced to brachytherapy for implant reconstruction and error detection. The manuscript briefly summarizes the main issues of EMT and error detection in brachytherapy. The potential and complementarity of EMT as treatment verification technology will be discussed in relation toin vivodosimetry and imaging.
EVALuna2:33051

On the use of multi-dimensional scaling and electromagnetic tracking in high dose rate brachytherapy - Goetz, Th I.; Ermer, M.; Salas-Gonzalez, Diego; Kellermeier, Markus; Strnad, Vratislav; Bert, Christoph; Hensel, Bernhard; Tome, A. M.; Lang, E. W. (Physics in Medicine and Biology, 2017)
High dose rate brachytherapy affords a frequent reassurance of the precise dwell positions of the radiation source. The current investigation proposes a multi-dimensional scaling transformation of both data sets to estimate dwell positions without any external reference. Furthermore, the related distributions of dwell positions are characterized by uni-or bi-modal heavy-tailed distributions. The latter are well represented by α-stable distributions. The newly proposed data analysis provides dwell position deviations with high accuracy, and, furthermore, offers a convenient visualization of the actual shapes of the catheters which guide the radiation source during the treatment.
EVALuna2:33032